CRISPR-Cas9 induced mutations along de novo purine synthesis in HeLa cells result in accumulation of individual enzyme substrates and affect purinosome formation - Baresova, Veronika; Krijt, Matyas; Skopova, Vaclava; Souckova, Olga; Kmoch, Stanislav; Zikanova, Marie (Molecular genetics and metabolism, 2016)
Purines are essential molecules for nucleic acid synthesis and are the most common carriers of chemical energy in all living organisms. The cellular pool of purines is maintained by the balance between their de novo synthesis (DNPS), recycling and degradation. DNPS includes ten reactions catalysed by six enzymes. To date, two genetically determined disorders of DNPS enzymes have been described, and the existence of other defects manifested by neurological symptoms and the accumulation of DNPS intermediates in bodily fluids is highly presumable. In the current study, we prepared specific recombinant DNPS enzymes and used them for the biochemical preparation of their commercially unavailable substrates. These compounds were used as standards for the development and validation of quantitative liquid chromatography-tandem mass spectrometry (LC-MS/MS). To simulate manifestations of known and putative defects of DNPS we prepared CRISPR-Cas9 genome-edited HeLa cells deficient for the individual steps of DNPS (CR-cells), assessed the substrates accumulation in cell lysates and growth media and tested how the mutations affect assembly of the purinosome, the multi-enzyme complex of DNPS enzymes. In all model cell lines with the exception of one, an accumulation of the substrate(s) for the knocked out enzyme was identified. The ability to form the purinosome was reduced. We conclude that LC-MS/MS analysis of the dephosphorylated substrates of DNPS enzymes in bodily fluids is applicable in the selective screening of the known and putative DNPS disorders. This approach should be considered in affected individuals with neurological and neuromuscular manifestations of unknown aetiology. Prepared in vitro human model systems can serve in various studies that aim to provide a better characterization and understanding of physiology and pathology of DNPS, to study the role of each DNPS protein in the purinosome formation and represent an interesting way for the screening of potential therapeutic agents.
Keywords: mutace; HeLa Cells; puriny; lidé; HeLa buňky; multienzymové komplexy; substrátová specifita; CRISPR-Cas systémy; tandemová hmotnostní spektrometrie; Chromatography, Liquid; Multienzyme Complexes; Tandem Mass Spectrometry; Mutation; chromatografie kapalinová; Substrate Specificity; Purines; CRISPR-Cas Systems; Humans